La naissance et la petite enfance en Nouvelle Angleterre à l'époque coloniale 1630-1750 - Bergamasco-Lenarda, Lucia (Revue d’histoire moderne et contemporaine, 1984)
Keywords: 1600-1699; 1700-1799; amériques; approches et analyses; colonialisme; colonisation britannique; condition de l'enfant; cours; discipline; enfance; famille; his4443; histoire; maternité; patriarcat; petite enfance; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis

Two serious ladies - Bowles, Jane (Dutton, 1984)
Two serious ladies who want to live outside of themselves, Christina Goering and Frieda Copperfield embark on separate quests of salvation. Mrs. Copperfield visits Panama with her husband, where she finds solace among the women who live and work in its brothels. Miss Goering becomes involved with various men. At the end the two women meet again, each transformed by her experience.
Keywords: amériques; approches et analyses; hétérosexisme; panama; personnes lesbiennes; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Feminity - Brownmiller, Susan (Linden/Simon and Schuster, 1984)
Avec intelligence et humour, Susan Brownmiller explore l'histoire et les règles tacites du fardeau de la « perfection féminine ». Qu'est-ce que la féminité ? Comment est-il mesuré ? Quelles sont ses revendications ? Comment les femmes sont-elles censées s'habiller, paraître, penser, agir, ressentir et être, selon les mœurs de la société ? Susan Brownmiller propose une critique pleine d'esprit et souvent pointue du concept de féminité dans la culture contemporaine et à travers l'histoire. Elle explore les exigences imposées aux femmes pour s'adapter à un moule établi, examine les stéréotypes féminins et célèbre les progrès durement gagnés dans le mode de vie et la tenue vestimentaire des femmes. À la fois profonde, révolutionnaire, stimulante et divertissante, Feminity défie la norme féminine acceptée tout en appréciant les femmes à travers l'histoire qui se sont courageusement libérées de ses contraintes.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; fem9000; inégalités; patriarcat; régions géographiques; systèmes d'oppressions; états-unis